Antioxidant Activity and Organoleptic Quality of Yellow Marigold Flower Kombucha (Tagetes erecta L.) on the Variations of Sugar Type and Fermentation Duration - Yessy, Herviana Yessykasari; Titik, Titik Suryani (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2025)
Kombucha is a fermented beverage made from a mixture of sweet tea using kombucha microbes known as SCOBY (Symbiotic Colony Of Bacteria and Yeast). One of the flowers that has the potential developed as kombucha ingredient is yellow marigold flower (Tagetes erecta L.). The purpose of this study was to determine the antioxidant activity and organoleptic quality of yellow marigold flower kombucha on variations of sugar types and fermentation duration. This study used an experimental method with a Completely Randomized Design (CRD) with 2 factors. Factor I: variation of sugar types (G): palm sugar and Javanese sugar. Factor II: fermentation duration (F): 5 days and 7 days. The results of the study showed that the highest antioxidant activity of yellow marigold flower kombucha was 71.44% in G1F2 treatment (200 g palm sugar and 7 days fermentation duration) and the highest organoleptic quality of yellow marigold flower kombucha was brown color, quite sour taste, quite aromatic type of kombucha and quite liked. in the G2F2 treatment (200 g palm sugar and 7 days fermentation duration).